2017
DOI: 10.1097/pec.0000000000000514
|View full text |Cite
|
Sign up to set email alerts
|

An Assessment of Newly Identified Barriers to and Enablers for Prehospital Pediatric Pain Management

Abstract: Top barriers to prehospital pediatric analgesic administration are related to skills and knowledge deficits, whereas enablers include support from agency leadership and personal views on analgesics. This information can be used to guide interventions to improve the management of pain in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 26 publications
0
21
0
1
Order By: Relevance
“…It is essential that prehospital providers have access to the resources required to facilitate pain management. Although more than half of the respondents identified that pain management is important, the influence of EMS and emergency department culture and leadership support on pain prioritisation and the provision of pain care in the prehospital setting must not be underestimated or overlooked (19,20).…”
Section: Barriers and Enablersmentioning
confidence: 99%
“…It is essential that prehospital providers have access to the resources required to facilitate pain management. Although more than half of the respondents identified that pain management is important, the influence of EMS and emergency department culture and leadership support on pain prioritisation and the provision of pain care in the prehospital setting must not be underestimated or overlooked (19,20).…”
Section: Barriers and Enablersmentioning
confidence: 99%
“…It is essential that prehospital providers have access to the resources required to facilitate the management of pain. Although more than half of respondents identified that pain management is important, the influence that organisational culture, EMS leadership support and emergency department culture and pain prioritisation may have on the provision of pain care in the prehospital setting must not be underestimated or overlooked (19,20).…”
Section: Barriers and Enablersmentioning
confidence: 99%
“…Male prehospital practitioners express more enduring (stoic) viewpoints regarding the need for analgesia while older practitioners have more negative attitudes about assessing pain medication requirements (30). Moreover, prehospital providers from various high-income countries (HIC) still report that pain assessment and management during undergraduate studies receive limited focus (18,20,21) and that continuous pain education is lacking (22). Knowledge, attitudes, and practices (KAP) surveys can be conducted to, measure what is known about a health problem, develop a baseline understanding of beliefs and behaviours, and even to quantify change after health interventions (31,32).…”
Section: Introductionmentioning
confidence: 99%